A device for the application of uniaxial strain to single crystal samples for use in synchrotron radiation experiments - Gannon, L. (2015)
We present the design, construction, and testing of a straining device compatible with many different synchrotron radiation techniques, in a wide range of experimental environments (including low temperature, high field and ultra-high vacuum). The device has been tested by X-ray diffraction on single crystal samples of quasi-one-dimensional Cs2Mo6Se6 and K2Mo6Se6, in which microscopic strains up to a Δc/c = 0.12% ± 0.01% change in the c lattice parameters have been achieved. We have also used the device in an inelastic X-ray scattering experiment, to probe the strain-dependent speed of sound ν along the c axis. A reduction Δν/ν of up to −3.8% was obtained at a strain of Δc/c = 0.25% in K2Mo6Se6.